A Novel Parameter Derived from Platelet Histograms: Pre-Peak to Post-Peak Ratio and Its Correlation with Platelet Recovery in Thrombocytopenic Patients - Gill, SS Gill; Batra, Harsh; Muralidharan, Shrikanth (Archives of Advances in Biosciences, 2026)
Background and Aim: Automated hematology analyzers generate platelet indices and histograms that can provide insight into platelet dynamics. This study evaluates a novel parameter—the pre-peak to post-peak ratio from platelet histograms—and its associations with the percentage of giant platelet, standard platelet indices, and clinical recovery in patients with thrombocytopenia. Methods: In an observational cohort study, 250 thrombocytopenic patients (platelet count <150,000/μL) were monitored over six days at a tertiary care center. Platelet histograms were analyzed using a 5-part automated hematology analyzer. The pre-peak/post-peak ratio was manually calculated, and its correlations with mean platelet volume (MPV), platelet distribution width (PDW), giant platelet percentage (from peripheral smears), and platelet recovery were assessed. Results: Hyper-destructive thrombocytopenia predominated (82.4%, n=206), with dengue identified as the leading cause (53.9%). In these cases, giant platelet percentages surged by day 3 (p<0.001), positively correlating with post-peak length and inversely with the ratio. The ratio declined on day 3 and rose on day 6 in 82.4% of recovering patients. In contrast, hypo-productive cases (17.6%, n=44) showed no significant changes or correlations. Conclusion: The pre-peak to post-peak ratio appears to be a simple and economical prognostic indicator for recovery in hyper-destructive thrombocytopenia, potentially guiding transfusion decisions and monitoring.